Transcriptomic Analysis of Chicken Lungs Infected With Avian and Bovine Pasteurella multocida Serotype A - Li, Pan; He, Fang; Wu, Chenlu; Zhao, Guangfu; Hardwidge, Philip R.; Li, Nengzhang; Peng, Yuanyi (Frontiers in Veterinary Science, 2020)
Pasteurella multocida (P. multocida) is a common animal pathogen responsible for many animal diseases. Strains from different hosts exhibit disparate degrees of effect in other species. Here, we characterize an avian P. multocida serogroup A strain (PmQ) showing high lethality to chickens and a bovine P. multocida serogroup A strain (PmCQ2) with no lethality to chickens. We used RNA-seq to profile the transcriptomes of chicken lungs infected with PmQ and PmCQ2. A total of 1,649 differentially expressed genes (DEGs) due to PmQ infection (831 upregulated genes and 818 downregulated genes) and 1427 DEGs (633 upregulated genes and 794 downregulated genes) due to PmCQ2 infection were identified. Functional analysis of these DEGs demonstrated that the TNF signaling pathway, the toll-like receptor signaling pathway, complement and coagulation cascades, and cytokine–cytokine receptor interaction were both enriched in PmQ and PmCQ2 infection. STAT and apoptosis signaling pathways were uniquely enriched by PmQ infection, and the NOD-like receptor signaling pathway was enriched only by PmCQ2 infection. Cell-type enrichment analysis of the transcriptomes showed that immune cells, including macrophages and granulocytes, were enriched in both infection groups. Collectively, our study profiled the transcriptomic response of chicken lungs infected with P. multocida and provided valuable information to understand the chicken responses to P. multocida infection.